2017
DOI: 10.5964/ejop.v13i1.1207
|View full text |Cite
|
Sign up to set email alerts
|

The perceived benefits of an arts project for health and wellbeing of older offenders

Abstract: The increasing ageing prison population is becoming a pressing issue throughout the criminal justice system. Alongside the rising population, are a host of health and wellbeing issues that contribute to older offenders needs whilst in prison. It has been recommended that meaningful activities can have positive effects on this population and therefore this paper uniquely reviews older offenders accounts of taking part in an arts based project, Good Vibrations, whilst imprisoned. The Good Vibrations project enga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 17 publications
3
32
0
Order By: Relevance
“…The intervention also brought forward the development of positive health behaviors, with it facilitating a daily routine. Participants reported benefits to their fitness and wellbeing, consistent with previous research that suggests an association between team sport and improved health outcomes (Eime et al, 2013) and the benefits of keeping inmates busy and occupied in meaningful pursuits (Wilkinson and Caulfield, 2017).…”
Section: Risk and Protective Factorssupporting
confidence: 83%
See 1 more Smart Citation
“…The intervention also brought forward the development of positive health behaviors, with it facilitating a daily routine. Participants reported benefits to their fitness and wellbeing, consistent with previous research that suggests an association between team sport and improved health outcomes (Eime et al, 2013) and the benefits of keeping inmates busy and occupied in meaningful pursuits (Wilkinson and Caulfield, 2017).…”
Section: Risk and Protective Factorssupporting
confidence: 83%
“…In line with the increasing number of interventions being provided in prisons to meet rehabilitation needs, recent research has examined the social, psychological and health benefits of prisonbased programs which include those focusing on arts, horticulture and vocational activities (Farrier et al, 2019;Wilkinson and Caulfield, 2017). The majority of these studies have demonstrated benefits in quality of life and reduced anxiety, depression and stress (Battaglia et al, 2013) as well as reduced rates of recidivism (Proctor et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the results of this study, the music workshop (Wilkinson and Caulfield, 2017) supported older prisoner's need to have a purpose, which included a musical performance or the creation of a Christmas tree. Furthermore, similar to the results of this study older prisoners attending True Grit (Harrison, 2006), art workshops (Hongo et al, 2015), and music interventions (Wilkinson and Caulfield, 2017) identified they were able to share their emotions, life experiences, their journey to prison, and traumatic stories. These interactions supported older prisoner's needs as well as supporting their fellow prisoners.…”
Section: Need To Have a Purposesupporting
confidence: 63%
“…Older prisoners within this study acknowledged the need to attend a prison initiative to support them to leave their cell, have a purpose and keep occupied. Other initiatives for older prisoners implemented have included art workshops (Hongo et al, 2015), music workshops (Wilkinson and Caulfield, 2017), and True Grit (Harrison, 2006;Kopera-Frye et al, 2013).…”
Section: Need To Have a Purposementioning
confidence: 99%
See 1 more Smart Citation